Influencia de las relaciones interpersonales en el clima organizacional de los trabajadores de la UGEL Sánchez Carrión - La Libertad. - Chavez Morante, Arlita Noemi (2013)
The present research is designed to determine the influence of interpersonal relationships on organizational climate UGELs workers Sánchez Carrión in order to analyze the relationships within the institution and propose solutions. To which gave the following scientific problem "How do the relationships in the organizational climate UGELs workers Sanchez Carrion?" Posing the following Hypothesis "interpersonal relations practiced properly by workers Sanchez Carrion UGELs lead a harmonious organizational climate", which was accepted. According to the study of materials and methods was determined as shown to all staff working at the Sanchez Carrion UGELs comprised 49 workers and as data collection instruments were designed interview from May 5 questions survey structure and questions of 23 items . Descriptive design was used Transectional square one, having as independent variable INTERPERSONAL RELATIONSHIPS, and as a dependent variable of organizational climate UGELs workers Sánchez Carrión. Result of this research found that there are good relationships between workers Sanchez Carrion UGELs which causes an unfavorable organizational climate that provides good performance and work among the staff working in this public institution.